The Meaning of Traditional Irrigation Management In Supporting The Establishment of Sustainable Agriculture in South Sumatra - Maya Sari; Muhammad Yazid; Dessy Adriani (Sriwijaya Journal of Environment, 2022)
One of the keys to the success in rural agriculture lies in the management of the irrigation system.  Irrigation in rural agriculture is closely related to social, cultural and environmental values of the village community.  This research is aimed at revealing the performance of traditional irrigation located in Pagaralam Vicinity and Lahat Regency, South Sumatra. . The results show that traditional irrigation still persists in the study area to this day, despite the modernization of the agriculture being promoted worldwide. This is evident from the discovery of social, cultural and environmental values among rural communities who currently still use traditional irrigation systems. The community still maintains the cultural values in the village in managing their traditional irrigation network such as the principle of mutual cooperation and deliberation which is the basis for managing village irrigation networks. Traditional irrigation has becomes one of the values that bonds the rural communities, especially farmers.